Larval morphology, development, and notes on the natural history of Cephaloleia “rolled-leaf” beetles (Coleoptera: Chrysomelidae: Cassidinae) - García-Robledo, Carlos; Horvitz, Carol C.; Staines, Charles L. (Zootaxa, 2010)
The Neotropical genus Cephaloleia Chevrolat, 1837 is comprised of 209 described species. Adults usually feed and mate within the scrolls formed by the young rolled leaves of plants of Neotropical Zingiberales. This paper reports for populations of Cephaloleia belti Baly, C. dilaticollis Baly, C. dorsalis Baly and C. placida Baly at La Selva Biological Station (Costa Rica, Central America) detailed descriptions of: 1. larval and adult diets and diet breadth; 2. egg, larval and pupal morphology; 3. larval development times; 4. dimorphic sexual characteristics; 5. adult longevity; and 6. differences in lifespan between genders. Cephaloleia belti displays the broader diet breadth, feeding on 14 species of three families of Zingiberales. Cephaloleia dilaticollis feeds on nine species of three families of Zingiberales. Cephaloleia dorsalis and C. placida feed on four species of Costaceae and two species of Zingiberaceae, respectively. Time to pupation ranges among species from 32.8 to 59.1 days. In the four Cephaloleia species, adult females are larger than males. Genders display marked sexual dimorphism in the shape of their last abdominal sternite and the pygidium. Longevity of adults ranged from ca. 300 to 390 days. Life expectancy estimates for adult beetles reared in the laboratory ranged from 111.5 to 187.2 days. Male and female adults of C. belti and C. dilaticollis have equivalent life expectancies. However, life expectancy is longer for male C. dorsalis and C. placida.